1993
DOI: 10.1093/eurheartj/14.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Acute closure during coronary excimer laser angioplasty and conventional balloon dilatation: a comparison of management outcome and prediction

Abstract: Of 523 consecutive patients undergoing elective percutaneous transluminal coronary angioplasty (PTCA) and 83 patients treated with coronary excimer laser angioplasty (ELCA), 17 (3.3%) had in-laboratory occlusion following PTCA and 25 (30%) following ELCA; they were enrolled into a prospective study. Successful management (reopened vessel, patency at repeat angiography within 24 h, no death, no myocardial infarction (MI), no emergency bypass surgery) including repeat lasing, subsequent PTCA, use of intracoronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Use of atherectomy and laser devices do not appear to increase safety by reducing abrupt closure rates. Rather, these devices were associated with an increased risk of abrupt closure that is consistent with findings in other studies [6,21,22]. In our investigation, these associations persisted after adjustment for other potential cofounding variables.…”
Section: Procedural Correlates Of Abrupt Closuresupporting
confidence: 92%
“…Use of atherectomy and laser devices do not appear to increase safety by reducing abrupt closure rates. Rather, these devices were associated with an increased risk of abrupt closure that is consistent with findings in other studies [6,21,22]. In our investigation, these associations persisted after adjustment for other potential cofounding variables.…”
Section: Procedural Correlates Of Abrupt Closuresupporting
confidence: 92%
“…Rather, these devices were associated with an increased risk of abrupt closure that is consistent with findings in other studies [6,21,22]. In our investigation, these associations persisted after adjustment for other potential cofounding variables.…”
Section: Procedural Correlates Of Abrupt Closuresupporting
confidence: 92%
“…Also of note were the rates of perforation (0.6%), dissection (5% with 3% being attributable to the laser), acute closure (0.6%), distal embolization (2.0%), and bleeding (3%), with laser therapy [29]. Studies in smaller laser volume centers have reported variable outcomes and adverse events, which may undermine the reliability of this technology [31–34]. Furthermore, one randomized trial using laser in addition to balloon angioplasty in unstable angina patients reported no difference in procedural success or outcome with laser use but a significant increase in procedural complications (18% vs. 3%; P = 0.0004), MI (4% vs. 0%; P = 0.04), and total in‐hospital MACE (10% vs. 4%; P = 0.08) with laser angioplasty [34].…”
Section: Thrombectomy Devicesmentioning
confidence: 99%